Consensus guidelines for antifungal stewardship, surveillance and infection prevention, 2021. (22nd December 2021) - Khanina, Anna; Tio, Shio Yen; Ananda‐Rajah, Michelle R.; Kidd, Sarah E.; Williams, Eloise; Chee, Lynette; Urbancic, Karen; Thursky, Karin A.; ,
Abstract: Invasive fungal diseases (IFD) are serious infections associated with high mortality, particularly in immunocompromised patients. The prescribing of antifungal agents to prevent and treat IFD is associated with substantial economic burden on the health system, high rates of adverse drug reactions, significant drug–drug interactions and the emergence of antifungal resistance. As the population at risk of IFD continues to grow due to the increased burden of cancer and related factors, the need for hospitals to employ antifungal stewardship (AFS) programmes and measures to monitor and prevent infection has become increasingly important. These guidelines outline the essential components, key interventions and metrics, which can help guide implementation of an AFS programme in order to optimise antifungal prescribing and IFD management. Specific recommendations are provided for quality processes for the prevention of IFD in the setting of outbreaks, during hospital building works, and in the context of Candida auris infection. Recommendations are detailed for the implementation of IFD surveillance to enhance detection of outbreaks, evaluate infection prevention and prophylaxis interventions and to allow benchmarking between hospitals. Areas in which information is still lacking and further research is required are also highlighted.